2010
DOI: 10.3144/expresspolymlett.2010.16
|View full text |Cite
|
Sign up to set email alerts
|

Linear low-density polyethylene/silica micro- and nanocomposites: dynamic rheological measurements and modelling

Abstract: Abstract. Linear low-density polyethylene (LLDPE) based composites were prepared by melt compounding with 1, 2, 3 and 4 vol% of various kinds of amorphous silicon dioxide (SiO2) micro-and nanoparticles. Dynamic rheological tests in parallel plate configuration were conducted in order to detect the role of the filler morphology on the rheological behaviour of the resulting micro-and nanocomposites. A strong dependence of the rheological parameters from the filler surface area was highlighted, with a remarkable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 57 publications
(86 reference statements)
7
67
0
Order By: Relevance
“…The latter part comes from filler-filler frictional interactions and G% confine stands for macromolecules intercalated in between clay layers. G% inter mainly contributes to the increase at low frequency of G% nano , particularly when clay content is above the percolation threshold [60][61][62]. Similar results were reported in the literature for PA12/NaMMT prepared by solvent intercalation.…”
Section: Rheologysupporting
confidence: 77%
“…The latter part comes from filler-filler frictional interactions and G% confine stands for macromolecules intercalated in between clay layers. G% inter mainly contributes to the increase at low frequency of G% nano , particularly when clay content is above the percolation threshold [60][61][62]. Similar results were reported in the literature for PA12/NaMMT prepared by solvent intercalation.…”
Section: Rheologysupporting
confidence: 77%
“…On the other hand, La Mantia et al [30] found that organomodified layered silicates did not have any effect on the crystallization properties of LLDPE fibers and hypothesized that the orientation in both crystalline and amorphous phases were similar for filled and unfilled fibers. According to our previous works on polyethylene based nanocomposites [20,21,23], we can hypothesize that the limited influence played by fumed silica nanoparticles on the crystallization properties of our HDPE matrix could be probably ascribed to their dispersion state. However, further investigations are needed to reach a deeper comprehension on the role played by nanosilica on the crystallization behaviour of polyethylene.…”
Section: Results and Discussion 31 Dsc And Dmta Resultsmentioning
confidence: 99%
“…The effect of silica and zirconia nanoparticles on the microstructure of LLDPE nanocomposites synthesized via in situ polymerization with zirconocene was investigated by Jongsomjit et al [17], while Wang et al [18] analyzed the dispersion behaviour of titania (TiO 2 ) nanoparticles in polyolefin nanocomposites. In recent years an extended investigation was carried out by this research group on the viscoelastic and the fracture behavior of polyolefin based nanocomposites [19][20][21][22][23]. It was found that the addition of small quantities of fumed silica nanoparticles could substantially improve both the failure properties and the creep stability of the investigated matrices.…”
Section: Introductionmentioning
confidence: 99%
“…An increase of the nanofiller amount promotes a reduction of the cell size and a consequent increase of the cell density, while opposite effects can be obtained increasing the foaming pressure. A quantitative evaluation of the cell size distribution was performed by using ImageJ software (U. S. National Institutes of Health, Bethesda, Maryland, USA) [44].…”
Section: Results and Discussion 31 Morphologymentioning
confidence: 99%